THE POTENTIAL AND SUCCESS OF EQUITY CROWDFUNDING IN INDONESIA: EXPLORING THE SIGNALING HYPOTHESIS AND FINANCIAL LITERACY CHALLENGES - Kosasih; Paramarta, Vip; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2024)
Stock crowdfunding has become an increasingly popular phenomenon in Indonesia, offering new opportunities for small and medium-sized enterprises (SMEs) to access capital by involving individual investors. However, the success of stock crowdfunding is uncertain and is related to several factors, including the use of signaling hypotheses by companies and the level of financial literacy among investors. This research aims to explore the potential and success of stock crowdfunding in Indonesia by examining signaling hypotheses and the financial literacy challenges faced. The research method used is qualitative, analyzing data from relevant journals, articles, and books. The results show that signaling hypotheses play a significant role in influencing investor interest and the success of stock crowdfunding campaigns. Companies that use positive signals, such as strong financial performance or the participation of prominent investors, tend to be more successful in attracting potential investors. However, financial literacy challenges, such as a lack of understanding of investment concepts and financial risks, are significant barriers to increasing participation and success in stock crowdfunding in Indonesia.